2004
DOI: 10.1590/s1413-70542004000100010
|View full text |Cite
|
Sign up to set email alerts
|

Resposta e níveis críticos de potássio para o arroz cultivado em solos de várzea inundados

Abstract: O presente trabalho foi conduzido em casa-de-vegetação do Departamento de Ciência do Solo da Universidade Federal de Lavras, no período de fevereiro a junho de 2002, com os objetivos de avaliar para o arroz (Oriza sativa L. cv. Jequitibá), cultivado em solos de várzea inundados, a resposta à adubação potássica e a contribuição das formas de K na nutrição, e estimar os níveis críticos do nutriente nos solos e na planta. O delineamento experimental utilizado foi o inteiramente casualizado, em esquema fatorial 4x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
1
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
1
1
5
Order By: Relevance
“…Similar results were observed by Mielniczuk & Selbach (1978) in soils of the state of Rio Grande do Sul. In other cases, boiling 1 mol L -1 HNO 3 can underestimate Kne, indicating a participation of non-exchangeable forms used by plants that are not extracted through this methodology (Nachtigall & Vahl, 1991;Silva et al, 2000;Cabbau et al, 2004;Villa et al, 2004). These results, as the ones observed in the present study, compromise the generalization of the use of boiling 1 mol L -1 HNO 3 as an index of Kne supply to plants.…”
Section: Resultsmentioning
confidence: 44%
“…Similar results were observed by Mielniczuk & Selbach (1978) in soils of the state of Rio Grande do Sul. In other cases, boiling 1 mol L -1 HNO 3 can underestimate Kne, indicating a participation of non-exchangeable forms used by plants that are not extracted through this methodology (Nachtigall & Vahl, 1991;Silva et al, 2000;Cabbau et al, 2004;Villa et al, 2004). These results, as the ones observed in the present study, compromise the generalization of the use of boiling 1 mol L -1 HNO 3 as an index of Kne supply to plants.…”
Section: Resultsmentioning
confidence: 44%
“…These data indicate that short-term supply of K in some soils depends of the release of K from non-exchangeable sources. In soils of Minas Gerais, Cabbau et al (2004) found that the exchangeable K and solution K were the pools that most contributed to the total K. This higher contribution of non-exchangeable pool to the total K observed in this study was due to no history of K fertilization of soils studied.…”
Section: Soil K Poolscontrasting
confidence: 45%
“…prontamente disponíveis para as plantas (VILLA et al, 2004;CABBAU et al, 2004). Entre os solos mais desenvolvidos, o teor de K não-trocável apresentou correlação positiva e elevada (Tabela 4) com a CTC efetiva (r = 0,95**), teor de silte (r = 0,97**) e relação silte/argila (r = 0,96**), mas para o grupo de solos menos desenvolvidos só foi verificada uma pequena correlação (r = 0,66*) entre os teores de K não-trocável dos solos e os teores de silte.…”
Section: Resultsunclassified
“…A forma com que o potássio (K) se liga à matéria mineral sólida do solo, bem como a energia dessas ligações, dá origem a diversas formas de K no solo: estrutural, trocável, não-trocável e solúvel (VILLA; FERNANDES; FAQUIN, 2004;CABBAU et al, 2004). Nos solos, as formas não-trocáveis, trocáveis e solúveis estão em equilíbrio dinâmico, de modo que qualquer alteração nos teores de K na solução do solo provocada pela adubação, absorção pela planta ou perda por lixiviação, irá alterar os teores das demais formas desse elemento no solo, principalmente das formas trocável e não-trocável.…”
Section: Introductionunclassified
See 1 more Smart Citation